SURVEI PERMAINAN TRADISIONAL DALAM PEMBELAJARAN PENJASORKES PADA SISWA DI SEKOLAH DASARSE- KECAMATAN BRANGSONG KABUPATEN KENDAL (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2014)
The purpose of this study was to determine the learning traditional game Penjasorkes at each school. The sampling technique used is total sampling method, the entire elementary school physical education teacher as Brangsong Kendal district, amounting to 18 people from 25 primary schools. Sampling techniques using random sampling or random sampling. Collecting data in this study using a survey method. Data collection techniques in this study is documentation and questionnaires. The results of the survey of traditional games in learning Penjasorkes on elementary school students in a district classified as good Brangsong Kendal is equal to 73.13%, the right to use in teaching elementary school students Penjasorkes on. Conclusion: surveys of traditional games in learning Penjasorkes on elementary school students in a district classified as good Brangsong Kendal and appropriate in elementary school students, it is evident from the existing indicators in view of the availability of time, availability of materials and learning penjas, game characteristics and the resulting motion, the elements penjas and motivation.